SYNTHESIS AND CHARACTERIZATION OF SILICA GEL/CHITOSAN COMPOSITE DERIVED FROM TIN TAILING FOR REMOVAL OF Fe(III) IN POST-TIN MINING WATER - Pilani, Rima; Nabila, Shagita; Vega; Verry Andre Fabiani (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
A study on the synthesis and characterization of silica gel/chitosan composite derived from tin tailings for removal of Fe(III) in post-tin mining water has been carried out. The silica source used for the synthesis of silica gel is tin tailings. It is produced by the sol-gel method. The characteristics of silica gel from tin tailings sand are white powder with a silica content of 73.58% after compositing with 30 mL and 45 mL chitosan solution, showing that the chitosan phase was successfully formed together with the silica phase. Functional group analysis showed the presence of typical chitosan functional groups (-NH2) at 1629 cm-1 and 1635 cm-1 and typical silica functional groups (-Si-O-Si) at 1000 cm-1 to 1020 cm-1. These functional groups appeared in addition to all variations of the chitosan solution. Morphological analysis shows that in the addition of 45 mL chitosan solution, the silica gel/chitosan composite has a morphology in the form of small round particles with uneven surfaces and more dominant pores. Adsorption study of silica gel/chitosan composite on Fe(III) in post-tin mining water showed 95.5% adsorption efficiency in the addition of 45 mL chitosan solution. The adsorption condition observed is the adsorption time as a fixed variable in this study, which is for 17 hours.